منصور حلاج کے مذہبی و متصوفانہ رخ کی مختلف پرتیں :جمیلہ ہاشمی کےناول" دشتِ سوُس" کاتجزیاتی مطالعہ (Al-Qamar, 2022)
The history of Urdu novel is incomplete without Jameela Hashmi’s Novels. She wrote great novels. Her first novel "Talāsh-e-Baharan" was full of romance. In this novel, she showed the romantic colors of life. She also used famous historical figures as subjects in her novels. These novels include "Chehra Ba Chehra Roo Ba Roo" and "Dasht-e-Soos". In " Chehra Ba Chehra Roo Ba Roo " the circumstances of the famous character Qurat-ul-Ain Tahira are discussed, while in "Dasht-e-Soos" the historical incident of Mansoor Hallāj is analyzed. The present article discusses this historical event regarding Mansoor Hallaāj
Keywords: Jameela Hashmi; Dasht-e-Soos; Mansoor Halaj